2018
DOI: 10.1002/jcla.22682
|View full text |Cite
|
Sign up to set email alerts
|

Application of Six Sigma for evaluating the analytical quality of tumor marker assays

Abstract: Context The results of detection assays for the same specimen are usually quite different in different laboratories or when tested with different detection systems. Objective This study was designed to investigate the value of applying sigma metrics derived from different standards for allowable total error (TEa) in evaluating the analytical quality of tumor marker assays. Methods Assays were evaluated for these six tumor markers: total prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…[16][17][18]20,21 The chart is divided into six grades by five lines. 22 Based on the sigma level, the performance of the analytes was divided into six grades 23 : worldclass (σ > 6), excellent (5 ≤ σ < 6), good (4 ≤ σ < 5), marginal (3 ≤ σ < 4), poor (2 ≤ σ < 3), and unacceptable (σ < 2) ( Figure 2). The sigma value of the analyte was represented by colored circles marked in certain sigma grades of the chart when the parameters of the analyte's name, TEa, bias, and CV were inputted into the interface.…”
Section: Construction Of the Normalized Qc Performance Decision Chartmentioning
confidence: 99%
“…[16][17][18]20,21 The chart is divided into six grades by five lines. 22 Based on the sigma level, the performance of the analytes was divided into six grades 23 : worldclass (σ > 6), excellent (5 ≤ σ < 6), good (4 ≤ σ < 5), marginal (3 ≤ σ < 4), poor (2 ≤ σ < 3), and unacceptable (σ < 2) ( Figure 2). The sigma value of the analyte was represented by colored circles marked in certain sigma grades of the chart when the parameters of the analyte's name, TEa, bias, and CV were inputted into the interface.…”
Section: Construction Of the Normalized Qc Performance Decision Chartmentioning
confidence: 99%
“…TEa represents the quality goals selected by the laboratory, and previous studies have shown that there are significant differences in sigma levels for the quality goals used for the same analytes in the same laboratories. 18,19 Thus, based on the model developed at the Milan Conference, 20 the desirable specification derived from biological variation was selected as the quality goal for cystatin C, and the sigma values were calculated based on the concentrations of two IQC materials. Our study found differences in the analytical performance for cystatin C at different concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical laboratories should regularly measure detection performance for all parameters and develop individualized quality control plans for all analytes to provide long-term, feasible measures for continuous improvement of assay quality. [11] Verma et al study reveals that if TE of an analyte is within allowable error limits specific for that analyte, bias % and CV % might be more reliable than sigma metrics. [12] TE for levels 1&2 shows the values did not exceed the allowable total error recommended by CLIA.…”
Section: Discussionmentioning
confidence: 99%